2021
DOI: 10.1049/nde2.12022
|View full text |Cite
|
Sign up to set email alerts
|

Greatly enhanced breakdown strength and energy density in ultraviolet‐irradiated polypropylene

Abstract: Polymer dielectrics have drawn great attentions for applications in advanced electronic devices and power grids because of their high breakdown strength, low dielectric loss, and excellent flexibility. However, the low energy density in polymer dielectric capacitors will hinder the continuous miniaturization of electrical systems. In this work, ultraviolet irradiation is demonstrated to greatly enhance the breakdown strength and energy density of polypropylene. Dramatically improved breakdown strength of 867 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…With the changes in RH, temperature and wind speed, the U oc of IL-GO/GO@PVA aerogels also show ladder-like changes (Figure 5c-e), indicating that the MEGs system can recognize different environments. [52][53][54] A self-powered strain sensing device is fabricated by encapsulating the aerogel containing water with polydimethylsuloxane. From Figures S39 and S40 (Supporting Information), when pressure is applied to the self-powered sensor, the water molecules in the aerogel are discharged, realizing the unidirectional flow of water molecules and generating voltage output in the self-powered sensor.…”
Section: Applicationsmentioning
confidence: 99%
“…With the changes in RH, temperature and wind speed, the U oc of IL-GO/GO@PVA aerogels also show ladder-like changes (Figure 5c-e), indicating that the MEGs system can recognize different environments. [52][53][54] A self-powered strain sensing device is fabricated by encapsulating the aerogel containing water with polydimethylsuloxane. From Figures S39 and S40 (Supporting Information), when pressure is applied to the self-powered sensor, the water molecules in the aerogel are discharged, realizing the unidirectional flow of water molecules and generating voltage output in the self-powered sensor.…”
Section: Applicationsmentioning
confidence: 99%
“…For BOPP-AA films, the dielectric constant is slightly higher than pristine BOPP films, which increases from 2.26 to 2.42 at 25 °C and 10 Hz. The introduction of polar groups, such as C=O and O-H on the surface of BOPP films, improves the polarization and leads to an increase in the dielectric constant [25][26][27][28] . Furthermore, the side groups of BOPP films are readily detached from the molecular chains after the UV irradiation treatment, especially as the UV irradiation period increases results in the increased dielectric constant, as seen in Figure S3.…”
Section: Dielectric Properties Of the Bopp-aa Filmsmentioning
confidence: 99%
“…Very recently, Chen et al reported that the E b of the PP film was greatly enhanced by UV irradiation, which resulted in chain scission and cross-linking. 16 Such an observation inspired us to explore the influence of ultraviolet radiation on the energy storage performance of the PVDF system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-energy radiation can improve the crystallinity in polymer materials and lead to the formation of a cross-linked network, thereby improving the dielectric/ferroelectric properties of PVDF. Very recently, Chen et al reported that the E b of the PP film was greatly enhanced by UV irradiation, which resulted in chain scission and cross-linking . Such an observation inspired us to explore the influence of ultraviolet radiation on the energy storage performance of the PVDF system.…”
Section: Introductionmentioning
confidence: 99%